Distribution of Parasitic Cestod "Ligula intestinalis" in Ma-zandaran Region - S Shargh; M Shamsaii; S Karimi (Iranian Journal of Parasitology, 2008)
Background: Ligulae intestinalis is a parasitic cestode, which has the economic-health importance in fishery industries. The aim of this study was to determine the prevalence of this parasite in Mazandaran. The effects of habitat temperature and kind of pool (sandy-cement) were considered as well.